2012
DOI: 10.4047/jap.2012.4.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic misfit of implant-supported prosthesis obtained by an alternative section method

Abstract: PURPOSEAdequate passive-fitting of one-piece cast 3-element implant-supported frameworks is hard to achieve. This short communication aims to present an alternative method for section of one-piece cast frameworks and for casting implant-supported frameworks.MATERIALS AND METHODSThree-unit implant-supported nickel-chromium (Ni-Cr) frameworks were tested for vertical misfit (n = 6). The frameworks were cast as one-piece (Group A) and later transversally sectioned through a diagonal axis (Group B) and compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…3,6,[10][11][12][13][14] Clinically acceptable misfit levels have been defined for fixed dental prostheses at between 50 and 120 mm. 3,[15][16][17] For computer-based restorations, a marginal gap of under 200 mm has been stated to be clinically acceptable. 7,18 Some studies have found that a marginal gap of under 100 mm is clinically acceptable.…”
mentioning
confidence: 99%
“…3,6,[10][11][12][13][14] Clinically acceptable misfit levels have been defined for fixed dental prostheses at between 50 and 120 mm. 3,[15][16][17] For computer-based restorations, a marginal gap of under 200 mm has been stated to be clinically acceptable. 7,18 Some studies have found that a marginal gap of under 100 mm is clinically acceptable.…”
mentioning
confidence: 99%
“…It is important to mention that there are other methods that could be used to improve the adaptation of one-piece casted frameworks, such as electroerosion and laser welding (12,13). These techniques are widely used and their effectiveness on improving fit of implant frameworks has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…A complete prosthetic treatment involves several clinical and laboratory procedures, such as impressions, cast/die pouring and prosthesis fabrication [1][2] . Errors can occur at any of these steps and may result in a prosthetic misfit 1,[3][4] . Therefore, the impression material plays an important role in minimizing errors when producing accurate replicas of the oral structures 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Errors can occur at any of these steps and may result in a prosthetic misfit 1,[3][4] . Therefore, the impression material plays an important role in minimizing errors when producing accurate replicas of the oral structures 1,4 . The elastomeric impression materials are materials with high accuracy and have been used in dentistry since the 1950s.…”
Section: Introductionmentioning
confidence: 99%